Debating planetary urbanization: For an engaged pluralism. (June 2018) - Brenner, Neil
This essay reflects on recent debates around planetary urbanization, many of which have been articulated through dismissive caricatures of the core epistemological orientations, conceptual proposals, methodological tactics, and substantive arguments that underpin this emergent approach to the urban question. Following consideration of some of the most prevalent misrepresentations of this work within this special issue, I build uponBarnes and Sheppard's (2010) concept of "engaged pluralism" to suggest more productive possibilities for dialogue among critical urban researchers whose agendas are too often viewed as incommensurable or antagonistic rather than as interconnected and, potentially, allied. The essay concludes by outlining nine research questions whose more sustained exploration could more productively connect studies of planetary urbanization to several fruitful lines of inquiry that have been explored within postcolonial, feminist and queer-theoretical strands of urban studies. While questions of positionality necessarily lie at the heart of any critical approach to urban theory and research, so too does the search for intellectual and political common ground that might help orient, animate and advance the shared, if constitutively heterodox, project(s) of critical urban studies.